Similar text sebagai Pengkodean Aplikasi Plagiarisme - Muhammad Wali; Safrizal Safrizal (KITA Institute, 2018)
This research is intended to make a coding technique with a function similar to a plagiarism detector similar_text as text. By using the text function is similar, this research resulted in a detection of the document against the 10 (ten) of selected journal with, the document is the document with extension doc, docx, pdf, and txt. The document will be converted into html form and would henceforth be done making the string with the marker dots (.) And the comma (,) will be fetched a new string. By specifying a percentage string similarity of 90% then produced a text, in this case plagiarism is detected journal journal 1 with string similarity percentage of 48%. The use of similar texts can be classified as coding techniques for detection of plagiarism on its anti plagiarism detection applications.